The Implementation of Family Nursing Care to Patients with Chronic Diseases: A Systematic Review - Aris Widiyanto; Santy Irene Putri; Asruria Sani Fajriah; Rejo Rejo; Isnani Nurhayati; Tri Yuniarti; Joko Tri Atmojo (STRADA : Jurnal Ilmiah Kesehatan, 2021)
A life-threatening illness can have an impact on the family system and family members often experience considerable physical, social, and emotional burdens. The purpose of this study was to examine the effectiveness of the implementation of family nursing care to patients with chronic diseases. This was a systematic review from online database such as BASE, Google Schoolar, and PubMed. There were 4 articles which declare that there are benefits on the implementation of family nursing care in increasing relationships for providing social support and escalating family ability to care for patients. 1 article suggest that there was no significant effect on the implementation of family nursing care to patients with chronic disease. There were 4 articles which declare that there are benefits on the implementation of family nursing care . 1 article suggest that there was no significant effect on the implementation of family nursing care.